Perbandingan Pengaruh Metode Peta Pikiran dan Peta Konsep pada Model Discovery Learning terhadap Hasil Belajar Peserta Didik Kelas VII SMP Negeri 18 Makassar (Studi pada Materi Pokok Pemanasan Global) - Nurfahmi Hamka; Ramlawati Ramlawati; Sitti Rahma Yunus (Celebes Science Education, 2022)
The purpose of research : (1) Determine score learning outcomes of students of VII Class SMPN 18 Makassar (Study on Global Warming) that learned using mind mapping method on discovery learning models, (2) Determine score learning outcomes of students of VII Class SMPN 18 Makassar (Study on Global Warming) that learned using concept mapping method on discovery learning models, and (3) Does the mind mapping method on discovery learning models have more influence on the learning outcomes of VII Class SMPN 18 Makassar (Study on Global Warming) compared to the concept mapping method on discovery learning models. This research is a Quasi Experimental by using a modified research design . The population of this study were all students of class VII of SMPN 18 Makassar . Sampling through purposive sampling technique and obtained class VII 1 as experimental class I and class VII 2 as experimental II. This research instrument is in the form of multiple choice learning outcomes in the form of 20 items that have been validated by experts. Data collection techniques in this study were the provision of pretest and posttest . Data analysis with descriptive statistics and inferential statistics. The results of inferential  analysis using t-test obtained that H0 is rejected by Ha is accepted so that it can be concluded that the learning outcomes of students who are taught using the mind mapping method are higher than the learning outcomes of students who are taught to use the concept mapping method.